The association between sexual health literacy and sexual function of women in Iran - Leila Dehghankar; Rahman Panahi; Marzieh Khatooni; Somayeh Fallah; Farnoosh Moafi; Mohammad Anbari; Fatemeh Samiei Siboni (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Considering the importance of sexual health literacy in promoting individual sexual health and ultimately improving family and social health as well as the effect of health literacy on sexual function, this study was designed and conducted to determine the association between sexual health literacy and sexual function among women. MATERIALS AND METHODS: This was a cross-sectional study. A total of 420 women referring to health centers were entered into the study using one-stage cluster sampling method. Data collection tools included a demographic questionnaire, Iranian Adult Sexual Health Literacy Assessment Questionnaire, and the Persian version of the Female Sexual Function Assessment Questionnaire (FSFI). Data were collected and entered into SPSS 22 and logistic regression. RESULTS: The results of the logistic regression test showed that the variable of sexual health literacy was effective on women's sexual function (P = 0.021) so that the chances of having a desirable sexual function in women with excellent were 4.222 times more than women with inadequate health literacy; the variables of employment status, level of education, duration of marital life, and the number of sexual intercourses per recent week were the factors affecting women's sexual function (P < 0.05). CONCLUSION: The results of this study pointed out the existence of an undesirable level of sexual function and a desirable level of sexual health literacy among participating women. Hence, designing and implementing the training plans to promote sexual function among these women is necessary.